A Study of Shi Pei’s Medical Ethics in “Yi Yi” - Lei, Heqing; Fu, Xinjun (Journal of Contemporary Medical Practice, 2025)
“Yiyi,” one of the six types and seven volumes of “Linglan Chuji,” is a treatise specifically discussing medical ethics, compiled by Shi Pei in the late Ming Dynasty, and is currently housed in the Cabinet Library of the National Archives of Japan. “Yiyi” is a specialized book with significant bibliographical and medical ethical value. This paper conducts a comprehensive study of its compilation background and the medical ethical thought it contains. The conclusion is that Shi Pei, in “Yiyi,” extensively cited works and treatises on medical ethics by medical practitioners and scholars from successive generations before the late Ming Dynasty, as well as relevant thoughts from the three schools of Confucianism, Buddhism, and Taoism, especially Confucianism. This was integrated with his experience accumulated during his long-term medical practice, providing an important and detailed reference for later generations to systematically study medical ethics. The traditional medical ethics described by Shi Pei in “Yi Yi” can be summarized into three aspects: Excellent skills and professional dedication, meaning that superb medical skills and a dedicated heart for practicing medicine serve as the foundation of medical ethics. Physicians should thoroughly study medical theories, improve their medical skills, and be prudent in medical practice; only then can they fulfill the responsibilities of a physician. Self-rectification of one’s own virtue, meaning that a physician’s moral cultivation must be noble, and they must possess a heart of universal love and benevolence for the world, never forgetting that medicine is fundamentally a benevolent art. Warnings and admonitions. Shi Pei cited Daoist and Buddhist doctrines to warn and admonish physicians to always remember their original intention of saving lives and healing the wounded.